Prevalence and Predictors of Nonadherence to Direct Oral Anticoagulant Treatment in Patients with Atrial Fibrillation - van der Horst, Sabine F. B.; de Vries, Tim A.C.; Chu, Gordon; Bavalia, Roisin; Xiong, Helen; van de Wiel, Kayleigh M.; Mulder, Kelly; van Ballegooijen, Hanne; de Groot, Joris R.; Middeldorp, Saskia; Klok, Frederikus A.; Hemels, Martin E.W.; Huisman, Menno V. (TH Open, 2023)
Background For most patients with newly diagnosed atrial fibrillation (AF), direct oral anticoagulants (DOACs) are preferred over vitamin K antagonists. However, there is concern that the lack of monitoring may impair therapy adherence and therefore the anticoagulant effect.Objective To assess 1-year DOAC nonadherence in patients with AF and a treatment indication of at least 1 year in the Dutch health care setting, and to identify predictors of nonadherence.Methods We performed a near-nationwide historical cohort study in patients with a novel DOAC indication for AF. Data were obtained from a pharmacy database, covering 65% of all outpatient prescriptions dispensed in the Netherlands. The 1-year nonadherence was assessed by the proportion of days covered; the threshold was set at <80%. Robust Poisson regression analyses were performed to identify predictors of nonadherence.Results A total of 46,211 patients were included and the 1-year nonadherence was 6.5%. We identified male sex (risk ratio [RR] 1.23, 95% confidence interval [CI]: 1.15–1.33), younger age (age ≥60 to <70 years: RR: 1.15, 95% CI: 1.00–1.33, age <60 years: RR: 2.22, 95% CI: 1.92–2.57; reference age ≥85 years), a reduced DOAC dose (RR: 1.10, 95% CI: 1.00–1.22), a twice-daily dosing regimen (RR: 1.21, 95% CI: 1.12–1.30), and treatment with apixaban (RR: 1.16, 95% CI: 1.06–1.26, reference rivaroxaban) or dabigatran (RR: 1.25, 95% CI: 1.14–1.37) as independent predictors of 1-year nonadherence.Conclusion One-year nonadherence to DOACs was low yet relevant in patients with AF newly prescribed a DOAC. Understanding the predictors for nonadherence may help identify patients at risk.
Keywords: direct oral anticoagulant; anticoagulants; medication adherence; atrial fibrillation